09/12/2007

factorizacion de trinomio por la forma ax2 + bx + c

4x2 + 8x + 3
= 4x2 + 6x + 2x + 3
= (4x2 + 6x) + (2x + 3)
= 2x(2x + 3) + (2x + 3)
= (2x + 1)(2x + 3)

2x2 + 5x + 3
= 2x2 + 3x + 2x + 3
= x(2x+3) + (2x + 3)
= (2x + 3) ( x + 1)

6x2 + 7x + 2
= 6x2 + 4x + 3x + 2
=2x(3x + 2)+(3x + 2)
=(2x + 1)(3x + 2)


6x2 + 5x - 4
= 6x2 + 8x - 3x - 4
= (6x2 + 8x) - (3x + 4)
= 2x(3x + 4) - (3x + 4)
= (2x - 1)(3x + 4)

6x2+17x+12
= 6x2 + 8x + 9x + 12
= (6x2 + 8x) + (9x + 12)
= 2x(3x + 4) + 3(3x + 4)
= (2x + 3)(3x + 4)

No hay comentarios.: